Astringent Food Compounds and Their Interactions with Taste Properties - Laaksonen, Oskar (fi=Turun yliopisto|en=University of Turku|, 2011)
Astringency is traditionally thought to be induced by plant tannins in foods. Because of this current research concerning the mechanism of astringency is focused on tannin‐protein interactions and thus on precipitation, which may be perceived by mechanoreceptors. However, astringency is elicited by a wide range of different phenolic compounds, as well as, some non‐phenolic compounds in various foods. Many ellagitannins or smaller compounds that contribute to astringent properties do not interact with salivary proteins and may be directly perceived through some receptors. Generally, the higher degree of polymerization of proanthocyanidins can be associated with more intense astringency. However, the astringent properties of smaller phenolic compounds may not be directly predicted from the structure of a compound, although glycosylation has a significant role. The astringency of organic acids may be directly linked to the perception of sourness, and this increases along with decreasing pH. Astringency can be divided into different sub‐qualities, including even other qualities than traditional mouth‐drying, puckering or roughing sensations. Astringency is often accompanied by bitter or sour or both taste properties. The different sub‐qualities can be influenced by different astringent compounds. In general, the glycolysation of the phenolic compound results in more velvety and smooth mouthdrying astringency. Flavonol glycosides and other flavonoid compounds and ellagitannins contribute to this velvety mouthdrying astringency. Additionally, they often lack the bitter properties. Proanthocyanidins and phenolic acids elicit more puckering and roughing astringency with some additional bitter properties. Quercetin 3‐O‐rutinoside, along with other quercetin glycosides, is among the key astringent compounds in black tea and red currants. In foods, there are always various other additional attributes that are perceived at the same with astringency. Astringent compounds themselves may have other sensory characteristics, such as bitter or sour properties, or they may enhance or suppress other sensory properties. Components contributing to these other properties, such as sugars, may also have similar effects on astringent sensations. Food components eliciting sweetness or fattiness or some polymeric polysaccharides can be used to mask astringent subqualities. Astringency can generally be referred to as a negative contributor to the liking of various foods. On the other hand, perceptions of astringent properties can vary among individuals. Many genetic factors that influence perceptions of taste properties, such as variations in perceiving a bitter taste or variations in saliva, may also effect the perception of astringency. Individuals who are more sensitive to different sensations may notice the differences between astringent properties more clearly. This may not have effects on the overall perception of astringency. However, in many cases, the liking of astringent foods may need to be learned by repetitive exposure. Astringency is often among the key sensory properties forming the unique overall flavour of certain foods, and therefore it also influences whether or not a food is liked. In many cases, astringency may be an important sub‐property suppressed by other more abundant sensory properties, but it may still have a significant contribution to the overall flavour and thus consumer preferences. The results of the practical work of this thesis show that the astringent phenolic compounds are mostly located in the skin fractions of black currants, crowberries and bilberries (publications I–III). The skin fractions themselves are rather tasteless. However, the astringent phenolic compounds can be efficiently removed from these skin fractions by consecutive ethanol extractions. Berries contain a wide range of different flavonol glycosides, hydroxycinnamic acid derivatives and anthocyanins and some of them strongly contribute to the different astringent and bitterness properties. Sweetness and sourness are located in the juice fractions along with the majority of sugars and fruit acids. The sweet and sour properties of the juice may be used to mask the astringent and bitterness properties of the extracts. Enzymatic treatments increase the astringent properties and fermented flavour of the black currant juice and decrease sweetness and freshness due to the effects on chemical compositions (IV). Sourness and sweetness are positive contributors to the liking of crowberry and bilberry fractions, whereas bitterness is more negative (V). Some astringent properties in berries are clearly negative factors, whereas some may be more positive. The liking of berries is strongly influenced by various consumer background factors, such as motives and health concerns. The liking of berries and berry fractions may also be affected by genetic factors, such as variations in the gene hTAS2R38, which codes bitter taste receptors (V).